2012
DOI: 10.7745/kjssf.2012.45.6.882
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Water Quality at Main Streams and Lake Doam in Daegwallyeong Area

Abstract: This study was surveyed that water physiochemical characteristics and phytoplankton incidence of main stream and Lake Doam near to Daegwallyeong agricultural area. Based on above results, it was conducted to get information overall water characteristics in south Han upstream river. COD value of Lake Doam was 6.1 mg L -1 and T-P (Total phosphorous) from there was 0.26 mg L -1 which was higher than the value of grade Ⅵ based on lake water living environment standard. Suspended solid was an average of 9.77 NTU wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Over the past two decades, the Doam-dam watershed has seen a significant reduction in observed discharges due to both anthropogenic activities and the effects of climate change. The rise in temperature and decrease in surface water by 25-45% in Korea have posed serious threats to water supplies and environmental sustainability [23]. Several studies have focused on pollutant changes and improving water quality in Doam Lake [6,24,25], but only a few have looked at the impact of climate change on streamflow for the watershed scale.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the Doam-dam watershed has seen a significant reduction in observed discharges due to both anthropogenic activities and the effects of climate change. The rise in temperature and decrease in surface water by 25-45% in Korea have posed serious threats to water supplies and environmental sustainability [23]. Several studies have focused on pollutant changes and improving water quality in Doam Lake [6,24,25], but only a few have looked at the impact of climate change on streamflow for the watershed scale.…”
Section: Introductionmentioning
confidence: 99%
“…And the use of chemical fertilizers and livestock manure is a great concern of non-point source pollutant discharge, as it deteriorates the ecology and environment of water bodies (Shin 2004, Heo et al 2006, Heo et al 2007). Park et al (2012) demonstrated that contamination in the water of Lake Doam and watershed streams was serious. Soil conservation to reduce SS and appropriate management are needed in the Lake Doam watershed to improve the water quality during wet weather conditions ).…”
Section: Introductionmentioning
confidence: 99%